Impact toughness of polypropylene/glass fiber composites: Interplay between intrinsic toughening and extrinsic toughening. (1st May 2016) - Yu, Bowen; Geng, Chengzhen; Zhou, Mi; Bai, Hongwei; Fu, Qiang; He, Bobing
Abstract: There are principally two mechanisms to improve the impact resistance of polymer-based composites, intrinsic toughening and extrinsic toughening. But the interplay between them is far from being well understood. Here, glass fiber was incorporated into polypropylene to promote extrinsic toughening mechanism, while addition of elastomer and annealing were adopted for intrinsic toughening. In this way, the interaction among glass fiber, elastomer and annealing could be discussed based on various characterizations, and their combined effect on mechanical properties of the composites could be determined. The results show that the intrinsic toughening mechanism of elastomer will be suppressed by glass fiber irrespective of the support of annealing, though annealing could work synergistically with glass fiber to toughen polypropylene. The possible structure-property relations are discussed. This work will provide deeper insight into the toughening behavior of polymer composites and practical guidance for the design of composites with excellent stiffness-toughness balance. Highlights: For the first time, the combined effects of elastomer and annealing on the toughness of polypropylene/glass fiber composites were investigated. The interplay between extrinsic toughening effect of glass fiber and intrinsic toughening effects of elastomer/annealing was discussed. A synergetic effect between GF extrinsic toughening and annealing-related toughening was demonstrated. The intrinsic toughening mechanism of elastomer will be suppressed by glass fiber irrespective of the support of annealing.